Biogeography and the structure of coral reef fish communities on isolated islands - Hobbs, Jean-Paul; Jones, G.; Munday, P.; Connolly, S.; Srinivasan, M. (Blackwell Publishing, 2012)
Aim To determine the applicability of biogeographical and ecological theory to marine species at two remote island locations. This study examines how biogeography, isolation and species geographic range size influence patterns of species richness, endemism, species composition and the abundance of coral reef fishes.Location Christmas Island and the Cocos (Keeling) Islands in the tropical eastern Indian Ocean.Methods Published species lists and underwater visual surveys were used to determine species richness, endemism, species composition and abundance of reef fishes at the islands. These data were statistically compared with patterns of species composition and abundance from the neighbouring ‘mainland’ Indonesian region.Results The two isolated reef fish communities were species-poor and contained a distinct taxonomic composition with an overrepresentation of species with high dispersal potential. Despite low species richness, we found no evidence of density compensation, with population densities on the islands similar to those of species-rich mainland assemblages. The mix of Indian and Pacific Ocean species and the proportional representations of the various regional faunas in the assemblages were not influenced by the relative proximity of the islands to different biogeographical provinces. Moreover, species at the edge of their range did not have a lower abundance than species at the centre of their range, and endemic species had substantially higher abundances than widespread species. At both locations, endemism was low (less than 1.2% of the community); this may be because the locations are not sufficiently isolated or old enough to promote the evolution of endemic species.Main conclusions The patterns observed generally conform to terrestrial biogeographical theory, suggesting that similar processes may be influencing species richness and community composition in reef fish communities at these remote islands. However, species abundances differed from typical terrestrial patterns, and this may be because of the life history of reef fishes and the processes maintaining isolated populations.